Evaluation of the genome in bird breeding - A. F. Yakovlev; N. V. Dement’eva (Вавиловский журнал генетики и селекции)
New technologies determining the DNA sequence of nucleotides have led to the discovery of hundreds of thousands of mononucleotide polymorphic markers, some of which are associated with breeding quality of animals. Developed on the basis of these achievements, genomic selection has produced a revolutionary shift in the poultry industry. The developed molecular marker system provides a unique opportunity to significantly improve the accuracy of estimated breeding values to manage genetic variability, to reduce the interval between generations, and accelerate genetic progress. Genomic breeding in the poultry industry has a number of differences from similar technology used in agricultural mammalian species. The existence of two categories of chromosomes (macro- and microchromosomes) with different rates of recombination, the preferred genomic females evaluation, rapid change of generations make their own features. Technology is introduced rapidly in various sectors of the poultry industry, including broiler production, and is used by major poultry companies. The individual steps of genomic selection need to be improved, and the continuous improvement of technology can be attained though its use in practical and scientific. The improvement of the separate stages of genome selection will be helped by perfection of registration and mathematical treatment of the phenotypical and molecular database, imputation and estimations of linkage disequilibrium.